Problems, Challenges and Prospects In Integrating ICT In English Language Teaching: Bangladesh Perspective - Talukder, Md. Jobaar; Liton Baron Sikder (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research paper explores the integration of Information and Communication Technology (ICT) in English Language Teaching (ELT) within the context of Bangladesh. The study delves into the various problems and challenges that educators face while incorporating ICT tools into ELT practices. It examines factors such as limited access to technology, inadequate digital literacy among teachers and students, and infrastructural constraints. The paper also highlights the potential benefits and prospects of utilizing ICT in ELT, including enhanced engagement, interactive learning opportunities, and exposure to authentic language resources. Drawing on qualitative data, the research aims to provide insights into the current status of ICT integration in ELT, shedding light on both barriers and opportunities. This analysis offers recommendations for addressing challenges and maximizing the benefits of ICT integration, thereby contributing to the improvement of English language education in Bangladesh's educational landscape.